Long run versus short run estimates of sustainable yield: a case of small-scale demersal fisheries in Oman - Bose, Shekar (2021)
This paper estimates both long- and short-run reference points under equilibrium and non-equilibrium bio-economic models for five commercially important demersal fish species from 1992 to 2016. The non-stationarity of catch-and-effort series, the statistical validity and the short-run dynamics of the conventional bio-economic equilibrium models were examined using co-integrating regression along with error-correction mechanism. The key findings are: Firstly, catch and effort series are I(1); secondly, the presence of long-run equilibrium relationship under the Schaefer and Fox models for each species are observed; thirdly, a significant short-run deviation was detected leading to the estimation of reference points under non-equilibrium situation; and, fourthly, the Friedman Test results (χ2 with 2 df = 6.40) indicated that overall, there were significant differences between the MSY results of the three models. Furthermore, a pair-wise comparison using a Wilcoxon Signed rank test (Z = -2.03, p = 0.042) showed that there was a significant difference between the MSY estimates of the Fox and nonequilibrium models only at 5 % level. Lastly, the equilibrium yield (MSY) for the summed single species model exceeded the aggregate model results by 21.4 % and 26.0 % for Schaefer and Fox models, respectively.